АЖИНИЁЗ ЛИРИКАСИДА СЎЗ МАЪНОСИ КЎЧИШИ УСУЛЛАРИ - Карлыбаева, Г.Е. (SCIENCE and SOCIETY, 2021)
The article is devoted to the semantic peculiarities of literary works of classic poet of Karakalpak literature Ajiniyaz. Polysemantic words, metaphors and metaphoric thinking are investigated. Peculiarities of using Polysemantic words is determined and there are given good examples of metaphors.